DEVELOPING A MODEL FOR ESTABLISHMENT OFTELE- DERMATOLOGYIN IRAN - Kazemi, Sakine Beygom; Jafari, Mehrnush; Hosseini, Seyed Mojtaba; Maher, Ali; Ba- hadori, Mohammadkarim (The journal of contemporary issues in business and government, 2021)
Background: Establishment of telemedicine and especially teledermatologyis quite challenging despite their numer- ous benefits.This requires an in-depth study of the key factors in this process using a valid and reliable instrument that is tailored to the culture of the studied population. Therefore, the purpose of the present research was to devel- opa modelfor establishment ofteledermatologyin Iran. Methods: Amixed-methods descriptive design was utilized in this study. The required data were collected using a custom questionnaire. A sample of 384 IT managers and experts in the field of dermatology completed the question- naire. To verify the validity and reliability of the instrument, Cronbach’s alpha as well as exploratory and confirma- tory factor analysis were used in LISREL 8.80 and SPSS 24, respectively, and Friedman test was used to rank the factors. Results:Based on the results of exploratory and confirmatory factor analysis, the key factors in the establishment of teledermatology in Iran included: provider (8 components), recipient (11components), economic (8 components), structural (6 components), technological (9 components), policy making (5 components), legal (6 components), and cultural (5 components) factors. Cultural factors had the greatest impact and economic factors had the least impact on establishment ofteledermatology in Iran. Conclusion: Theproposed model consisting of 8 factors can serve as a useful and comprehensive guide for policy- making and decision-making on how to establishteledermatology.